Routine circumcision? The role of prepuce in syndactyly repair. Issue 4 (August 2020) - Romeus, Laniel; Liu, Cherry; Stanton, Robert; Ellsworth, Pamela
Summary: Circumcisions are among the most commonly performed procedures in the pediatric population, but the value of the preputial skin often goes unrecognized as a potential graft (Ehrlichman et al., 2018). We highlight three patients who underwent coordinated circumcision and use of the excised preputial skin as a graft for syndactyly repair. Syndactyly, a condition where fingers are fused together, is often repaired utilizing skin from the groin region, which can result in unwanted hair growth and subcutaneous fat growth. The utilization of the prepuce is a convenient alternative that may have fewer undesirable qualities. Summary Fig. Patient with polysyndactyly Summary Figure